2013
DOI: 10.1186/1471-2229-13-71
|View full text |Cite
|
Sign up to set email alerts
|

Fast-tracking development of homozygous transgenic cereal lines using a simple and highly flexible real-time PCR assay

Abstract: BackgroundA crucial step in the evaluation of newly produced transgenic plants is the selection of homozygous plants. Here we describe an efficient and highly flexible real-time PCR-based method for the development of homozygous lines in plant models with complex (multiple) genomes and/or relatively long generation times (>3 months) using direct copy number determinations.ResultsAn existing DNA extraction method was converted into a high-throughput plant leaf DNA extraction procedure yielding DNA suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…In addition, none of the qPCR-based method has been utilized for gene stacking to show the accuracy highly consistent among qPCR, genetic segregation, and Southern Blotting analysis [7][8][9]19]. Our results indicated that our protocol not only was more effective and accurate than previously published qPCR methods, but also offered the distinct advantages of relative simplicity, rapid screening, and comparable accuracy over traditional methods such as Southern Blotting and previously published qPCR methods.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, none of the qPCR-based method has been utilized for gene stacking to show the accuracy highly consistent among qPCR, genetic segregation, and Southern Blotting analysis [7][8][9]19]. Our results indicated that our protocol not only was more effective and accurate than previously published qPCR methods, but also offered the distinct advantages of relative simplicity, rapid screening, and comparable accuracy over traditional methods such as Southern Blotting and previously published qPCR methods.…”
Section: Discussionmentioning
confidence: 73%
“…New primers were developed for TaAmy3 following the procedures described in Mieog et al (2013); TaAmy3FP: TTCTTTTCCAGGGGTTTAATTGGG, TaAmy3RP: CTCCACCTTCCCTTGCATGA.…”
Section: Methodsmentioning
confidence: 99%
“…DNA for copy number analyses was extracted and homeoform-specific primer pairs for TaAMY4, and isoformspecific primers (but not homeoform-specific) pairs for TaAMY1 and 2, were developed and tested as described in Mieog et al [25]. Plasmids containing clones for each homeoform of TaAMY4 as well as for Epsilon Cyclase genome A, obtained during sequencing procedures, were used to make a mixed plasmid sample, which was used as a calibrator sample for TaAMY4 homeoform copy number determinations.…”
Section: Sequencing Dna and Rna Extractions And Pcr Analysesmentioning
confidence: 99%
“…Amylase-isoform specific primers for real-time quantitative PCR (RT-qPCR) were developed for TaAMY1, 2 and 4 as previously described for qPCR [25]. TaAMY3 primers as well as primers for a reference housekeeping gene (actin) were already available [17].…”
Section: Sequencing Dna and Rna Extractions And Pcr Analysesmentioning
confidence: 99%